Wideband frequency-reconfigurable antenna for sub-6 GHz wireless communication - Tandel, Tejal; Trapasiya, Samir (International Journal of Reconfigurable and Embedded Systems (IJRES), 2025)
This paper presents a compact dual-band frequency-reconfigurable monopole antenna for sub-6 GHz wireless applications. Using a single PIN diode, the antenna switches between 2.7 GHz and 3.9 GHz bands, achieving bandwidths of 472 MHz and 1130 MHz, respectively, with peak gains up to 1.65 dB. The demand for smaller devices has driven the development of compact antennas capable of operating across multiple bands. The main benefits of this antenna include its compact size, enhanced bandwidth, and design simplicity, which is achieved by integrating slots into the patch and introducing a tiny slot etched over the ground plane. The antenna is created using an FR4 material with a thickness of 1.6 mm and dimensions of 25×15 mm². The antenna prototype was fabricated and tested to validate its performance. Simulation optimization reveals that the antenna operates with a gain of 0.9–1.65 dB and a bandwidth of (472–1130 MHz). The design also achieves a VSWR of less than 1.3 and a radiation efficiency between 74% and 78%. The performance enhancement of the reconfigurable antenna was fine-tuned utilizing microwave solvers in both computer simulation technology (CST) and advance design system (ADS).